1997
DOI: 10.1177/096032719701600502
|View full text |Cite
|
Sign up to set email alerts
|

Presence of methenamine/glutathione mixtures reduces the cytotoxic effect of sulphur mustard on cultured SVK-14 human keratinocytes in vitro

Abstract: 1 The basal epidermal keratinocytes of the skin are a main target for the vesicating agent, sulphur mustard (SM). A human keratinocyte cell line (SVK-14) has been used to model the effects of SM on the basal epidermal keratinocytes and subsequently to test the efficacy of potential prophylactic compounds in reducing the SM-induced cytotoxicity. 2 The cultures were pretreated with mixtures of methe namine (HMT) and glutathione (GSH) for 1 h prior to exposure to 10 μM SM. The viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Therefore, supplementing GSH or its precursors, including NAC, could help minimize this oxidative stress and reduce HD/CEES-caused toxicity, although its associated mechanism and defined biological systems are not well known (Amir et al, 1998;Atkins et al, 2000;Han et al, 2004;Arfsten et al, 2007;Paromov et al, 2007Paromov et al, , 2008. The protective role of extracellular GSH is highlighted in a study using the macrophage monocyte cell line J774 as well as in the mitotically active SVK 14 keratinocyte cell line (Smith et al, 1997;Amir et al, 1998). Using the biomarker we recently established in JB6 and HaCaT cells (Tewari-Singh et al, 2010), our present study demonstrates both the protective and therapeutic efficacy of GSH in attenuating CEES-caused cytotoxic responses; however, the protective efficacy was greater than its rescue potential in terms of DNA synthesis and cell cycle progression parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, supplementing GSH or its precursors, including NAC, could help minimize this oxidative stress and reduce HD/CEES-caused toxicity, although its associated mechanism and defined biological systems are not well known (Amir et al, 1998;Atkins et al, 2000;Han et al, 2004;Arfsten et al, 2007;Paromov et al, 2007Paromov et al, , 2008. The protective role of extracellular GSH is highlighted in a study using the macrophage monocyte cell line J774 as well as in the mitotically active SVK 14 keratinocyte cell line (Smith et al, 1997;Amir et al, 1998). Using the biomarker we recently established in JB6 and HaCaT cells (Tewari-Singh et al, 2010), our present study demonstrates both the protective and therapeutic efficacy of GSH in attenuating CEES-caused cytotoxic responses; however, the protective efficacy was greater than its rescue potential in terms of DNA synthesis and cell cycle progression parameters.…”
Section: Discussionmentioning
confidence: 99%
“…HD/CEES-caused oxidative stress results in the 8-oxo-2-deoxyguanosine DNA adduct as well as lipid and protein oxidation, which can cause inflammation and other toxic responses in skin Black et al, 2010). The exogenous addition of antioxidants such as GSH, N-acetyl cysteine (NAC), vitamin E, superoxide dismutase, catalase, sulforaphane, quercetin, and catalytic antioxidants such as manganese (III) meso-tetrakis (di-N-ethylmidazole)porphyrin (AEOL 10150) has been reported to attenuate lung and skin injury by HD/CEES (Gross et al, 1993;Smith et al, 1997;Amir et al, 1998;Han et al, 2004;Arfsten et al, 2007;Paromov et al, 2007Paromov et al, , 2008Gould et al, 2009;Black et al, 2010;O'Neill et al, 2010). Whereas most of these efficacy studies with antioxidants indicate that they have beneficial effects in attenuating HD/ CEES-caused lung injury, there are few, if any, reports of efficacy studies with GSH and its associated mechanism of action in relevant skin epidermal cells and skin toxicity models of HD/CEES (Paromov et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that it may be important also in the repair of bulky lesions induced by HD. Previous reports have suggested that the capacity of HD to induce DNA damage places limits on the efficacy of approaches aimed at protecting human cells from the cytotoxic effects of HD using scavenging agents such as hexamethylenetetramine Smith et al, 1997;Andrew and Lindsay, 1998a), mono-isopropylglutathione Andrew and Lindsay, 1998b) and di-isopropylglutathione (Lindsay and Hambrook, 1998). In addition, the use of protease inhibitors such as E64 and mafenide hydrochloride (Lindsay et al, 1996) has been shown to prevent dermo-epidermal separation in human skin explants exposed to HD but did not prevent the degradation of basal epidermal keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Sulfur mustard exposure of the human keratinocyte cell line SVK-14 is accompanied by decreased viability. 11 Pretreatment with glutathione increased the survivability of SVK-14 cells exposed to HD. Pretreatment of cultured rat lung slices with cysteine esters, which raise cellular cysteine levels available for glutathione synthesis, is reported to be protective in HD injury.…”
Section: Introductionmentioning
confidence: 99%